Exploring The Relationship between Project-Based Learning and Collaborative Skills: EFL Learners’ Voices - Santi Andriyani; Syafiul Anam (Al-Lisan: Jurnal Bahasa, 2022)
This research aims to measure EFL learners' perceived project-based learning and examine whether there is a correlation between project-based learning and EFL learners' collaborative skills. This research used a correlational study using Spearman Product Moment based on non-parametric data. The data were gathered using a closed-ended questionnaire. The sample consisted of 100 (17 male and 83 female) Indonesian University EFL learners recruited using convenience sampling. The findings indicated that more than 70% of learners' perceptions of project-based learning positively impact their collaborative skills. The benefits of project-based learning include enhancing learners' motivation, teamwork, communication, creativity, and problem-solving abilities. The next finding is a strong correlation between project-based learning, which significantly generated Sig. (p-value) = 0.000 < α = 0.05. Some previous studies reported that project-based learning positively correlates with collaborative skills.